1999
DOI: 10.1159/000055553
|View full text |Cite
|
Sign up to set email alerts
|

Localised Fibre Cell Swelling Characteristic of Diabetic Cataract Can Be Induced in Normal Rat Lens Using the Chloride Channel Blocker 5-Nitro-2-(3-Phenylpropylamino) Benzoic Acid

Abstract: Chloride channels are known to be involved in the regulated volume decrease that occurs when the rat lens is exposed to hypotonic challenge. We now report that chloride channel blockage makes the rat lens gain water under isotonic conditions, suggesting that chloride and water fluxes may also play an important role under resting conditions. Histological comparison of hypotonically and isotonically swollen rat lenses revealed a significant difference: in the former, fibre cells were swollen from the periphery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…Our finding that an anion conductance dominates the membrane properties of longer isolated fiber cells is consistent with earlier experiments that reported modulation of resting lens voltage by extracellular Cl Ϫ removal (1, 3, 15), a series of morphological studies on whole lens organs cultured under isosmotic conditions that were exposed to a variety of anion channel inhibitors (8,40,51,55), and patch-clamp studies that previously detected anion channel activity in isolated fiber cells and excised membrane patches (54,56). In this study, we demonstrate, for the first time, that isolated fiber cells and whole lenses share a common lyotropic anion selectivity sequence (Table 3).…”
Section: Discussionsupporting
confidence: 90%
“…Our finding that an anion conductance dominates the membrane properties of longer isolated fiber cells is consistent with earlier experiments that reported modulation of resting lens voltage by extracellular Cl Ϫ removal (1, 3, 15), a series of morphological studies on whole lens organs cultured under isosmotic conditions that were exposed to a variety of anion channel inhibitors (8,40,51,55), and patch-clamp studies that previously detected anion channel activity in isolated fiber cells and excised membrane patches (54,56). In this study, we demonstrate, for the first time, that isolated fiber cells and whole lenses share a common lyotropic anion selectivity sequence (Table 3).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have suggested that rat lens volume is regulated over the course of 48 h, with maximal swelling occurring at 12-18 h post osmotic challenge (Patterson and Fournier 1976;Tunstall et al 1999). This time point was therefore selected to investigate the eVect of osmotic stress on lens wet weight, transparency, and Wber cell morphology (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 More recently, the role that Cl Ϫ ions play in this process has been further investigated by culturing rat lenses in the presence of a range of Cl Ϫ channel inhibitors, including 5-nitro-2-(3-phenylpropylamino) benzoic acid (NPPB). [3][4][5] In these experiments, exposure of lenses cultured under both hypotonic and isotonic conditions to Cl Ϫ channel inhibitors produced an increase in lens volume. 3 This indicates that, under normal isotonic conditions, a constitutively active flux of Cl Ϫ ions exists in the lens that regulates fiber cell volume and thereby maintains lens transparency.…”
mentioning
confidence: 99%
“…[3][4][5] In these experiments, exposure of lenses cultured under both hypotonic and isotonic conditions to Cl Ϫ channel inhibitors produced an increase in lens volume. 3 This indicates that, under normal isotonic conditions, a constitutively active flux of Cl Ϫ ions exists in the lens that regulates fiber cell volume and thereby maintains lens transparency.…”
mentioning
confidence: 99%